The impact of rapid urbanization on water resources based on INLA - Song, Yongjun; Wang, Huimin; Lu, Qingkai; Ma, Chen; Wang, Jinke; Gan, Feng; Zhang, Siqin; Xu, Haojun; Zhao, Zimeng (Frontiers in Environmental Science, 2025)
Rapid urbanization reshapes regional water resources by reconfiguring land systems and altering the balance between runoff and infiltration. Empirical evidence that jointly accounts for human and natural drivers while addressing spatial dependence remains limited. Using harmonized 1-km data for the Beijing–Tianjin–Hebei region during 2014–2023, including land use from CLCD, nighttime lights from VIIRS, and precipitation, this study combines Sen–Mann–Kendall trend detection with spatial models estimated by Integrated Nested Laplace Approximation. The results show that urbanization, measured by nighttime lights, has a consistently stronger association with water resource related land change than precipitation. The interaction between precipitation and nighttime lights is place specific and positive in Beijing and Shijiazhuang, with coefficients of 0.0622 and 0.1579, which indicates amplification of urbanization linked land conversion under wetter conditions. The integrated framework distinguishes human and climatic signals and reveals spatial heterogeneity that is relevant to water sensitive urban planning.